Large' vs. 'small' players: a closer look at the dynamics of speculative attacks - Geir H. Bjønnes; Steinar Holden; Dagfinn Rime; Haakon Olav Aarstrand Solheim (Center for Economic Studies and ifo Institute (CESifo), 2009)
What is the role of large players like hedge funds and other highly leveraged institutions in speculative attacks? In recent theoretical work, large players may induce an attack by an early move, providing information to smaller agents. In contrast, many observers argue that large players are in the rear. We propose a model that allows both the large player to move early in order to induce speculation by small players, or wait so as to benefit from a high interest rate prior to the attack. Using data on net positions of large (foreigners) and small (locals) players, we find that large players moved last in three attacks on the Norwegian krone (nok) during the 1990s: The ERM-crisis of 1992, the NOK-pressure in 1997, and after the Russian moratorium in 1998. In 1998 there was a contemporaneous attack on the Swedish krona (sek) in which large players moved early. Interest rates did not increase in Sweden so there was little to gain by a delayed attack.
Keywords: F31; F41; G15; 330; Speculative attacks; microstructure; international finance; large players; Devisenspekulation; Internationaler Finanzmarkt; Devisenhandel; Marktstruktur; Schätzung; Norwegen; Schweden